Estimation of distribution of suprema of a strictly ?-sub-Gaussian quasi shot noise process - Vasylyk, O. I. (Київський національний університет імені Тараса Шевченка, 2019)
In this paper, there are studied properties of a strictly ?-sub-Gaussian quasi shot noise process X(t) = integral_{-?}^{+?} g(t, u) d?(u), t ? R, generated by the process ? and the response function g. New estimates for distributions of suprema of such processes are derived. An example of application of the obtained results is given.Key words: shot noise processes, distrubution of suprema of a process, ?-sub-Gaussian processes.Pages of the article in the issue: 8 - 17Language of the article: Ukrainian